Influência de pontas de pulverização e adjuvantes no potencial de redução de deriva em túnel de vento - Chechetto, Rodolfo Glauber [UNESP]; Antuniassi, Ulisses Rocha [UNESP]; Mota, Alisson Augusto Barbieri [UNESP]; Carvalho, Fernando Kassis [UNESP]; Silva, Anne Caroline Arruda [UNESP]; Vilela, Caroline Michels [UNESP] (Universidade Estadual de Londrina, 2013)
The drift is intimately linked to inappropriate use of pesticides and an important factor for reducing it, is the correct selection of spray nozzles and adjuvants. The objective of this work was to evaluate the drift potential in wind tunnel with different spray nozzles and different concentrations of adjuvants. The experiment was composed by six spray solutions (vegetable oil (in three concentrations), mineral oil, surfactant and reducing drift), which were applied with two nozzles, one pre-orifice flat fan (DG 8003 VS) and other with air induction (AI 8003 VS), totaling 12 treatments, with three repetitions. The equipment used was a wind tunnel, where the drift collections were made at different points. The treatments averages were compared using Confidence Interval at 5% probability. The analysis of the percentage of drift showed that the treatments had different behaviors. The nonylphenol ethoxylate adjuvant presented the highest drift when applied with the nozzle of pre-orifice and the lowest drift when applied with the air induction. The behavior of these nozzles when the oil-based adjuvant was used showed apposite results to those obtained for the surfactant. For the DG nozzles the lowest percentage of drift, at all analyzed distances, was observed to the treatment with vegetable oil (1.0%) and with the AI nozzles the lower drift was found for the treatment with nonylphenol ethoxylate (0.0625%), for the four distances in the collection. The result showed that both the spray nozzles and adjuvants alter directly the drift potential. There was no proportionately between the concentration of the oil-based adjuvant and the drift percentage.
Influence of spray nozzles and adjuvants in drift reduction potential in wind tunnel
Keywords: Application technology; Mineral oil; Surfactant; Vegetal oil